CRITERIA AND INDICATORS FOR IMPROVING THE EMPLOYMENT AND WELL-BEING OF THE POPULATION IN RURAL AREAS - Usmonov Murodbek Dusmurot o‘g‘li (Scholars Digest Publishing, 2023)
This article reflects on the practical issues that drive the discussion on the criteria and indicators of employment and welfare of the population in residential areas. The article is to explore and recommend the possibilities of accelerating the population, improving prospects and helping the population to update the location.
Keywords: Areas of employment, population employment, well-being, perspective, location and location indicators, infrastructure, education, innovation, network organizations.